La Raza Lawyers Banquet - Watkins, Howard::::::::: (1983)
Betsy Temple, Hilda Cantu-Montoy, Joel Murillo, and David Hernandez standing behind Joanne Cordova, Rachel Nunez and Judge Ralph Nunez at head table